QUEST on DASI: a South Pole CMB polarization experiment - Church, Sarah; Ade, Peter A. R.; Bock, James; Bowden, Melanie; Carlstrom, John; Ganga, Ken; Gear, Walter Kieran; Hinderks, James; Hu, Wayne; Keating, Brian; Kovac, John; Lange, Andrew; et al. (New Astronomy Reviews, 2003)
QUEST on DASI is a ground-based, high-sensitivity, high-resolution (ℓmax∼2500) experiment designed to map CMB polarization at 100 and 150 GHz and to measure the power spectra from E-modes, B-modes from lensing of the CMB, and B-modes from primordial gravitational waves. The experiment comprises a 2.6 m Cassegrain optical system, equipped with an array of 62 polarization-sensitive bolometers (PSBs), located at the South Pole. The instrument is designed to minimize systematic effects; features include differencing of pairs of orthogonal PSBs within a single feed, a rotatable achromatic waveplate, and axisymmetric rotatable optics. In addition the South Pole location allows both repeatable and highly controlled observations. QUEST on DASI will commence operation in early 2005.